Creating Community through Church-based Pollinator Gardening - Dohe, Carrie B. (Worldviews, 2024)
Bees for Peace promotes pollinator protection by establishing blooming feeding sites for bees and other pollinators on the grounds of houses of worship. In Canada, the project’s primary aim was to educate people about native bees, invoking positive feelings that moved people to protect these relatively unfamiliar creatures. To do so, I developed fun, educational games and talks on the cultural history of bees, which I presented at numerous churches in the Greater Toronto Area. Despite ongoing challenges posed by the COVID-19 pandemic, the project and its student researchers were able to partner with two churches to plant pollinator gardens. The educational activities that accompanied the care and maintenance of these gardens resulted in individuals in and around the churches experiencing an expanded sense of community as well as a heightened awareness of native pollinators and the desire to protect them.